Análisis ergonómico de los equipos de protección personal que utiliza el Cuerpo de Bomberos del cantón Bolívar - Calderón Castro, Mónica Lizeth (2025)
Occupational safety has become a crucial factor in workers' performance. This research aimed to analyze the ergonomic risks associated with the personal protective equipment (PPE) used by the Fire Department in Bolívar canton. The methodology included bibliographic, field, and descriptive research, along with deductive, inductive, and observational methods. Information collection techniques such as interviews and surveys were employed. Additionally, tools such as the Likert scale and Google Forms were used, allowing for the consolidation of relevant data to achieve the stated objectives. It is important to note that the data collection instruments were designed and validated using the CVC method, ensuring the accuracy and validity of the data obtained. Based on the results, an improvement plan was proposed using the 5W+1H matrix. The findings revealed various issues affecting comfort and performance during work activities, leading to muscular pain. Furthermore, it was observed that the PPE was not in optimal condition to ensure worker safety. Consequently, it is essential for the institution to implement the proposed improvement plan to mitigate ergonomic risks for operational workers and guarantee high-quality service to the community.